Promoting learner autonomy : a comprehensive online guide for English teachers in Iceland - Óskar Finnur Gunnarsson 1985- (2021)
In this project, I demonstrate how teaching language learning strategies helps students achieve learner autonomy and become more efficient language learners. First, I cover the different types of language learning strategies and how they can be used while learning a new language. I then explore the concept of learner autonomy and describe the relationship between language learning strategies and learner autonomy. Following this, I include short interviews with English teachers to better understand the general knowledge of language learning strategies as applied in the Icelandic English teaching community, and to understand how teachers are using them. The interviews also proved insightful in terms of a deeper insight into the main challenges of the language learning classrooms. These insights guided the direction of the final project, as it was adapted to address the real needs of English teachers. The final outcome was the creation of a practical website for English teachers that includes lesson plans for teaching and practicing language strategies in the classroom. The website also serves as a tool to introduce teachers to language learning strategies, the concept of learner autonomy, and a detailed review of a comprehensive framework for achieving learner autonomy: the European Language Portfolio.